Open abdomen management for severe peritonitis in elderly. Results from the prospective International Register of Open Abdomen (IROA): Cohort study. (October 2020) - Rausei, Stefano; Pappalardo, Vincenzo; Ceresoli, Marco; Catena, Fausto; Sartelli, Massimo; Chiarugi, Massimo; Kluger, Yoram; Kirkpatrick, Andrew; Ansaloni, Luca; Coccolini, Federico; ,; Montori, Giulia; et al.
Abstract: Background: Analyzing the data of the International Register of Open Abdomen (IROA), the feasibility of open abdomen treatment has been demonstrated at every age. This new analysis on the IROA database investigates the risk factors for mortality in elderly patients treated with open abdomen for intra-abdominal infection. Methods: Data were derived from the IROA, a prospective observational international cohort study that enrolled patients treated with open abdomen worldwide. A univariate analysis of potential risk factors was performed. Inclusion criteria were patients older than 65 years and treated with open abdomen for intra-abdominal infection. End point was overall mortality, calculated within 30 days after open abdomen management, after 1-month and 1-year follow-up. Results: A total of 116 patients was analyzed with mean age of 76 ± 7 years. Definitive closure was achieved in 93 patients (93/116, 80.2%) for a mean open abdomen duration of 5.0 ± 5.0 days. Complicated patients were 101 (101/116, 87.1%) for a total of 201 complications. Overall, 62 out of 116 patients (53.4%) died: 23 patients (23/62, 37.1%) during open abdomen management, 29 patients (46.8%) within 30 days after abdominal closure, 9 patients (14.5%) after 1-month follow-up, and 1 patient (1.6%) after 1-year follow-up. Age did not affect mortality (75 ± 6 years in alive patients versus 77 ± 7 years in dead patients, p = 0.773). Definitive abdominal closure was the most important factor to prevent mortality. Conclusions: This study confirmed that age alone cannot be considered a determinant for death, even in elderly patients managed with open abdomen for severe intra-abdominal infection. Highlights: Open abdomen management is a treatment option to be considered for intra-abdominal infection also in elderly patients. Definitive abdominal closure is the most important factor to prevent mortality in these cases. In this setting age alone cannot be considered a determinant for death.